1995
DOI: 10.1111/j.1432-2277.1995.tb01481.x
|View full text |Cite
|
Sign up to set email alerts
|

FK 506 versus cyclosporin in the prevention of renal allograft rejection – European pilot study: six-week results

Abstract: FK 506 was compared with cyclosporin in a randomised trial in good-risk cadaveric renal transplant recipients. The objective was to evaluate whether oral FK 506 dosing was viable and whether blood concentrations in the range 10-20 ng/ml would prove to be practical. Thirty-one adult patients were randomised to FK 506 and 16 to cyclosporin. Both groups received an identical regimen of azathioprine and corticosteroids. Serum creatinine concentrations decreased rapidly in both groups with mean values below 200 mum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…Although mean arterial pressure was comparable, the need for anti-hypertensive drugs was lower in the tacrolimus group and more patients were without anti-hypertensive treatment. This is in accordance with previous reports in which tacrolimus was compared to both Sandimmune [17,33,40,42] and Neoral [19].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although mean arterial pressure was comparable, the need for anti-hypertensive drugs was lower in the tacrolimus group and more patients were without anti-hypertensive treatment. This is in accordance with previous reports in which tacrolimus was compared to both Sandimmune [17,33,40,42] and Neoral [19].…”
Section: Discussionsupporting
confidence: 82%
“…In our study, renal function in patients with a functioning graft 12 months after transplantation was comparable with tacrolimus and Neoral. This is in accordance with previous reports in which tacrolimus was compared to Sandimmune [17,26,33,40,42,52] or Neoral [lo, 291. In contrast, Jurewicz reported a lower serum creatinine in the tacrolimus group than in the Neoral group [19].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In prospective and historically controlled studies of primary therapy, tacrolimus has generally demonstrated greater efficacy than the conventional formulation of cyclosporine A (CyA) in preventing episodes of acute rejection and allowed a reduction in corticosteroid use. 5,6 Acute rejection rates were also significantly reduced with tacrolimus in a large-scale randomized study of kidney transplantation. 7 Although short-term graft survival is similar on tacrolimus and CyA, tacrolimus is also an effective rescue therapy for renal allograft rejection during CyA therapy.…”
Section: Introductionmentioning
confidence: 99%